2007
DOI: 10.1097/jcp.0b013e31802e0002
|View full text |Cite
|
Sign up to set email alerts
|

Does Fluoxetine Have Any Effect on the Cognition of Patients With Mild Cognitive Impairment?

Abstract: Fluoxetine enhanced memory and cognition in the patients. This was consistent with previous studies that emphasized the role of fluoxetine in improving memory and promoting neurogenesis in the hippocampus. However, this is a preliminary study with small sample size, and larger double-blind placebo-controlled studies are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(67 citation statements)
references
References 16 publications
2
61
1
3
Order By: Relevance
“…As principais melhoras parecem associadas às funções de memória de trabalho (Dí-gitos e Sequência de Números e Letras), raciocínio abstrato (Raciocínio Matricial), atenção, concentração, velocidade de processamento cognitivo (Procurar Símbolos e Códigos) e raciocínio espacial (Cubos). Estudos têm relatado a capacidade da fluoxetina de induzir neurogênese no hipocampo, com consequente melhora cognitiva nas funções de memória (Li et al, 2009;Mowla, Mosavinasab, & Pani, 2007), o que parece sustentar os presentes achados. Teng, Humes, Nakata e Melzer (2008) e Ogren et al (2008) também já haviam apontado que a estimulação do sistema serotoninérgico aparentemente está relacionada à melhora da cognição.…”
Section: Resultsunclassified
“…As principais melhoras parecem associadas às funções de memória de trabalho (Dí-gitos e Sequência de Números e Letras), raciocínio abstrato (Raciocínio Matricial), atenção, concentração, velocidade de processamento cognitivo (Procurar Símbolos e Códigos) e raciocínio espacial (Cubos). Estudos têm relatado a capacidade da fluoxetina de induzir neurogênese no hipocampo, com consequente melhora cognitiva nas funções de memória (Li et al, 2009;Mowla, Mosavinasab, & Pani, 2007), o que parece sustentar os presentes achados. Teng, Humes, Nakata e Melzer (2008) e Ogren et al (2008) também já haviam apontado que a estimulação do sistema serotoninérgico aparentemente está relacionada à melhora da cognição.…”
Section: Resultsunclassified
“…Greater anterior cingulum pathology in people with MCI and AD has been associated with more irritability, agitation, dysphoria, apathy, and night time behavioral disturbances 94 . Serotonergic dysfunction is probably of particular relevance to NPS, including depression and aggression 95 , suggesting serotonergic drugs might theoretically treat NPS and reduce risk of progression; in one preliminary study fluoxetine improved cognition in people with MCI compared with placebo after 8 weeks 96 . We found that depressive symptoms predicted conversion from any type MCI to all cause dementia in epidemiological studies, but evidence from clinical studies was inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…The antidepressant fluoxetine is a powerful stimulant of hippocampal neurogenesis (Malberg et al, 2000) and improves memory deficits in patients with mild cognitive impairment (Mowla et al, 2007), and after traumatic brain injury (Horsfield et al, 2002). In animal models, fluoxetine-induced neurogenesis is associated with improved allocentric spatial learning and memory after ischaemic injury (Li et al, 2009), and restoration of deficits in spatial working memory after anti-mitotic treatment (ElBeltagy et al, 2010;Lyons et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%